Effects of social dominance orientation and right‐wing authoritarianism on corrupt intention: The role of moral outrage. (11th February 2015) - Tan, Xuyun; Liu, Li; Zheng, Wenwen; Huang, Zhenwei
Abstract : Previous research suggested that dominance orientation and authoritarianism may be associated with corruption, but little research has verified this assumption or uncovered its psychological processes. In this article, we examined empirically the relationships between social dominance orientation (SDO), right‐wing authoritarianism (RWA) and corrupt intention and explored the mediating role of moral outrage on these relationships. A total of 677 college students participated in the study and completed measures of SDO, RWA, moral outrage and corrupt intention. Our findings demonstrated that both SDO and RWA were positively associated with corrupt intention. Additionally, moral outrage partially mediated the relation between SDO and corrupt intention and fully mediated the relation between RWA and corrupt intention. Specifically, the results indicated that higher SDO or RWA was associated with reduced moral outrage and increased corrupt intention. This implies that the enhancement of morality and moral outrage may inhibit corrupt intention.